Moving Through the Ancient Cultural Landscape of Mangaia (Cook Islands) - Reilly, Michael P.J. (Waka Kuaka, 2018)
A cultural landscape is pregnant with memories of the past that are remembered and retold through oral traditions. These memories include the movements of the ancestors through their natural world: how they orientated themselves within their landscape, the paths they took to travel from one place to another and the many kinds of journeys they embarked upon, such as ritual and mourning processions, expeditions to war, escapes to refuges, trips to access natural resources or jaunts to enjoy entertainments. This paper explores these movements as they are remembered within the cultural landscape of Mangaia in the Cook Islands.